A description and examination of cyber‐bullying victimisation in the UK. Issue 3 (4th September 2021) - Tzani, Calli; Ioannou, Maria; Synnott, John; McDonnell, Dean; Pylarinou, Ntaniella‐Roumpini
Abstract: Cyber bullying (CB) might be relatively new in comparison to School‐Bullying (SB); nonetheless, both types have a negative impact on victims' psychological state. This project investigated CB in the UK and examined the victimisation means, as well as the reasons behind it. Four hundred and eight participants completed an online survey, which includes the 52‐item measure Cyber‐bullying and Online Aggression survey (CBOAS). The survey was advertised on social media and was active for nine months. From the sample, 37.26% reported that they had experienced CB victimisation more than once. Females seem to be more frequently involved in CB, particularly on Facebook and by spreading rumours. Such incidents usually result from arguments in real‐life settings. Many victims were able to stop their CB victimisation by standing up to their CB perpetrators. There are indications that CB functions as a subtype of SB. Implications and limitations are discussed in detail.